Transcriptome Analyses Reveal Adult Metabolic Syndrome With Intrauterine Growth Restriction in Pig Models - Shen, Linyuan; Gan, Mailin; Zhang, Shunhua; Ma, Jideng; Tang, Guoqing; Jiang, Yanzhi; Li, Mingzhou; Wang, Jinyong; Li, Xuewei; Che, Lianqiang; Zhu, Li (Frontiers in Genetics, 2018)
Epidemiological data has indicated that intrauterine growth retardation (IUGR) is a risk factor for adult metabolic syndrome. However, the causative genetic mechanism leading to the phenotype in adulthood has not been well characterized. In the present study, normal and IUGR adult pigs were used as a model system to survey differences in global gene expression in livers through transcriptome sequencing. The transcriptome libraries generated 104.54 gigabases of data. In normal and IUGR pigs, 16,948 and 17,078 genes were expressed, respectively. A total of 1,322 differentially expressed genes (DEGs) were identified. Enrichment analysis of the DEGs revealed that the top overrepresented GO terms and pathways were related to oxidoreductase activity, ATPase activity, amino catabolic process, glucose metabolism and Insulin signaling pathway. The increased gluconeogenic and decreased glycogen synthesis in the liver contributed to the glucose intolerance observed in IUGR. The reduced expression of insulin signaling genes (such as PI3K and AKT) indicated an elevated risk of diabetes in adulthood. Together, these findings provide a comprehensive understanding of the molecular mechanisms of adult IUGR pigs as well as valuable information for future studies of therapeutic intervention in IUGR metabolic syndrome.